A descontinuidade do ciclo da inovação - Lobo, Rodrigo Cortopassi Goron (2017)
It is common sense in the Academy and in organizational environments that innovation is critical to both business evolution and development and that lack of innovation can halt the competitive edge of an organization. This situation becomes even more serious with the organizations themselves being unaware of the circumstances that lead to the interruption of the innovation cycle. This research work aims to present a solution to this problem, through the identification of the innovation management process within organizations, in order to point out what leads to a possible interruption of the innovation cycle. It was developed from a comprehensive study of exploratory and qualitative nature, using the multiple case study method with a hierarchical taxonomic model, which grounded the construction and analysis of semantic networks derived from empirical data. The result was the identification of drivers for the innovation cycle interruption, revealed in two groups of organizations: the first group, called Alfa, composed of organizations mostly reactive to the mainstream of the industry, and the second group, called Beta, composed of proactive organizations in relation to the mainstream. The drivers are the motivations for the cycle interruption, which for the Alpha Group were the perception that products or activities will not have proper financial return (insufficiency of the business case); Regulatory compliance overlapping superior performance; The constant fulfillment of regulatory goals inhibiting innovation and technological advancement; Concentration of innovation decisions in a small group of people; Conservative governance. For Beta Group the motivations were the potential imprisonment in existing processes (maintenance of the status quo); Weak management of technology portfolio and R & D; The collapse of factors associated with innovation; The "institutional cholesterol"; Accommodation in a consecrated and/or highly successful commercial model; And the untying from an innovative mentality.